The acute effects of loading used in wearable resistance on kinetics and kinematics during taekwondo axe kick - Janep, M.; Osman, N.; Mohamad, N. I.; Tan, K.; Malik, Z. A.; Nadzalan, A. M. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2024)
Background. Wearable resistance (WR) is used in sports training with the aim of increasing performance by enabling sport-specific movements to occur with additional loading. Problem and aim. Despite its potential to allow athletes to move more specifically, studies examining WR during kicking in taekwondo are scarce. The purpose of this study is to determine the acute effects of loading in WR on the kinetics and kinematics during taekwondo axe kicks. Material and methods. Thirty (N=30) university taekwondo athletes have been recruited as participants in this study. Participants performed a middle axe kick with WR loading worn at the lower body (0%, 5%, 10%, and 15% of body mass) during the execution. A high-speed motion capture system was used to analyse kinematic data (kicking velocity and kicking time) while the force plate was used to measure ground reaction force (GRF). Results. Results showed there was a significant change in kicking kinematics (kicking time was longer and there was a decrease in kicking velocity) as the WR load increased. There was a significant increase of GRF on the supporting leg as WR loads attached increased. Conclusions. In conclusion, WR loading of 5% body mass and higher at the lower body affected the biomechanics of the middle axe kick. Although mechanically affected the movement, future studies are suggested to investigate the chronic effects of these loading. The implications of this study can be used as a guideline for choosing proper WR loading to be used in training.